Kelp-inspired N–I-doped ZnO photocatalysts with highly efficient catalytic activity. (1st March 2016) - Cai, Aijun; Du, Liqiang; Wang, Qian; Chang, Yongfang; Wang, Xiuping; Guo, Xuemin
Abstract: Efficient N–I-doped ZnO photocatalysts with hierarchical structures are fabricated with kelp as the template. Abundant nitrogen and iodine are successfully simultaneously introduced into the bulk ZnO crystals though calcination under high temperature (600 °C). The morphology, structure, composition, and optical absorption properties of the kelp-templated ZnO are characterized by X-ray diffraction (XRD), field-emission scanning microscopy (FESEM), transmission electron microscopy (TEM), and diffuse reflectance spectra (DRS), respectively. The band gap of the kelp-templated ZnO is narrowed by the N–I coping. The photocatalytic activity under UV-irradiation of the kelp-templated ZnO is about 23.1 times and 1.1 times that of common ZnO and P25, respectively. In addition, no obvious activity of the kelp-templated ZnO is decreased, during five cycle runs. The efficient photocatalytic activity of the kelp-templated ZnO is attributed to the sufficient UV-light utilization and efficient separation of electron–hole pairs.